Causes of death and poor survival prognostic factors in Thai patients with systemic sclerosis - Ruangjutipopan S. (2014)
Causes of death and poor prognostic factors for patients with systemic sclerosis (SSc) were studied in 222 cases. Their mean age at the onset and duration of disease was 48.9 ± 12.0 years and 23.3 ± 29.3 months, respectively. Fifty-three per cent were diffuse subtype. Patients with diffuse SSc had more digital pitting scars and more muscle, heart, lung, and esophageal involvement than those with limited subtypes (p ≤ 0.02). One hundred and six patients were lost to follow-up. With a median follow-up duration of 25 months, 31 of the remaining 116 patients (26.7%) died. SSc related death occurred in 18 cases, in which the lung, heart and kidney (renal crisis) were the major causes. Infection contributed to the remaining 13 deaths. When compared with living patients, using a univariate analysis, factors associated with a reduced survival rate were age of > 45 years at the onset, diffuse skin thickness, and lung, gastrointestinal tract, heart, kidney and muscle involvement (p ≤ 0.001). In the multivariate analysis, only age of > 45 years at onset and cardiac involvement remained poor prognostic factors (p = 0.04 and 0.001, respectively).